Program Human resource Development untuk Mengembangkan Kompetensi Pendidik pada PAUD Mutiara Bantul, Yogyakarta - Hayati, Firdha; Munastiwi, Erni (Jurnal Golden Age, 2021)
The increasingly number of integrated Early Childhood Education institutions, requires Early Childhood Education managers to be more observant and sensitive in improving the quality of education, both in terms of teacher competence, infrastructure and learning processes that are of selling value. In this study, Early Childhood Education managers are required to improve the competence and professionalism of human resources. This study aims to find out how Integrated Early Childhood Education Institution Mutiara Bantul develops the competence of educators through human resource development program. This research is a qualitative descriptive study. In this study, data were collected using interviews and documentation. The results of this study state that to develop the competence of educators through human resource development program, Early Childhood Education Institution MutiaraÂ  has implemented a variety of programs, namely a) trading educators to Integrated Early Childhood Education Institution, b) Advanced Studies and c) facilitating educators by involving educators into various Early Childhood Education teacher competency training.